Spiritual Well-being and Its Relationship With Academic Achievement in Iranian College Students: A Systematic Review - Fatemeh Hosseinzadeh; Farideh Namadi; Nabi Akbarnezhad; Esmayil Zeynali; Moradali Zareipour (نشریه پرستاری ایران)
Background & Aims Spiritual well-being (SWB) is a key factor for improving students’ quality of life and well-being. This study aims to investigate the SWB status in Iranian college students and assess its relationship with academic achievement. Materials & Methods This is a systematic review study. To find the information, a search was conducted in the databases of Web of Science, Scopus, PubMed, Google Scholar, Scientific Information Database (SID) and MagIran for Persian and English articles published between 2000 and 2024 using the keywords academic performance, student, Iran, academic achievement, spiritual health and SWB. Initially, the search yielded 168 articles. After removing duplicates and screening the titles, abstracts, and full texts of the studies, 13 articles were finally included in the review. Results Most of the studies reported an moderate level of SWB in Iranian students, and a significant positive correlation between their SWB and academic achievement. The students with higher levels of SWB tended to have better academic performance. Conclusion Attention to the SWB of Iranian students can be an effective strategy for enhancing their academic achievement. It is recommended that educational and counseling programs provided in the Iranian universities have a more focus on improving the students’ SWB.